Dashboards for Monitoring Program Impact in Mental Health Advocacy Non-profits - Chikaome Chimara Imediegwu; Okeoghene Elebe (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The growing demand for transparency, accountability, and data-driven decision-making in the nonprofit sector has elevated the importance of dashboards as strategic tools for monitoring program impact, particularly within mental health advocacy organizations. These nonprofits face unique challenges, such as measuring non-clinical outcomes, engaging diverse stakeholders, and operating with limited resources. This review explores how digital dashboards can be leveraged to enhance real-time monitoring, streamline impact reporting, and drive strategic learning across mental health advocacy initiatives. Drawing on multidisciplinary literature, the paper examines the design principles, technological architectures, and implementation strategies that support effective dashboard use. It also discusses ethical considerations, data quality concerns, and capacity-building efforts required to sustain impactful dashboard use in resource-constrained environments. The review concludes with future directions for integrating artificial intelligence, interoperability, and participatory evaluation techniques to advance evidence-based advocacy and equitable mental health outcomes.